Immunohistochemistry on decalcified rat nasal cavity: trials and successes. (September 2013) - Harris, Nancy; Carter, Charleata A; Misra, Manoj; Maronpot, Robert
Abstract : Immunohistochemical (IHC) staining for Casein Kinase 2 alpha (CK2a), cyclin-dependent kinase inhibitor 1B (p27Kip1), and heat shock protein 90 (HSP90) was performed on four levels of decalcified rat nasal cavity from four male and three female controls following nose-only exposure to ambient air for 5 days. Successful staining with negligible background artifact was obtained on multiple epithelial and neuroepithelial soft tissues, without antigen retrieval. Independent optimization was needed for each of the three antibodies. A major challenge in this project was maintaining tissue adherence to the slides during tissue incubations. This report documents immunolocalization of CK2a, p27Kip1, and HSP90 in respiratory and olfactory tissue of the rat nose.